Vegetative parameters of apple cultivars in integrated and organic production systems - Dremák, P.; Csihon, Á.; Gonda, I. (International Journal of Horticultural Science, 2016)
Success of apple production is highly influenced by the applied production system and the planted cultivar. In this paper growing characteristics of 39 apple cultivars were studied in integrated and organic production systems. These kind of parameters are less studied in the cultivar and training system examinations, although they have huge effect on the training and maintaining of canopy, on the pruning necessity, ultimately on the production costs. According to our results the thickness of the central axis of apple trees showed significant differences between the integrated and the organic systems. Axis of the trees with lower trunk thickness tapers more slightly in the integrated production system, than in the case of the trees with thicker trunk in the organic system. Thicker axis is not accompanied by thicker trunk, namely the thickness of the central leader starts to decrease stronger in the organic production system, compared to the integrated one.